2021
DOI: 10.5005/jp-journals-10071-23915
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Profile of Prosthetic Valve Endocarditis due to Candida parapsilosis: An 11-year Retrospective Observational Study from a Quaternary Cardiac Referral Institute in India

Abstract: Background: Recent changes in the diagnostic criteria and the introduction of newer technologies like prosthetic valve replacement require the need to identify the changing epidemiology of prosthetic valve endocarditis (PVE). Materials and methods: This is a retrospective, cross-sectional, observational study. Patients diagnosed with Candida parapsilosis definite and possible PVE as per modified Duke’s criteria for a period of 11 years from January 2010… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…One study showed that the mean age of Indian patients with infective endocarditis caused by C. parapsilosis sensu stricto was 52 years [25]. In eastern China, nearly twice as many men as women have been infected with C. parapsilosis sensu stricto in the past 15 years, with an average age of approximately 54 years [6].…”
Section: Discussionmentioning
confidence: 99%
“…One study showed that the mean age of Indian patients with infective endocarditis caused by C. parapsilosis sensu stricto was 52 years [25]. In eastern China, nearly twice as many men as women have been infected with C. parapsilosis sensu stricto in the past 15 years, with an average age of approximately 54 years [6].…”
Section: Discussionmentioning
confidence: 99%
“…Thirty series could be identified. There is a large variation in the rates of fungal IE, which ranges from less than 1% [10][11][12][13][14][15][16] , between 1% and 2% [17][18][19][20][21][22][23][24][25][26][27][28][29] , between 2% and 5% [30][31][32][33][34] , to over 5% [35][36][37][38][39] . The latter series included patients with an immune compromised state such as after transplantation [36] or with prosthetic valves [38,39] .…”
Section: Rate Of Fungal Microorganisms In the Included Series Of Infe...mentioning
confidence: 99%
“…Most authors group all fungal IE in one category [13,[15][16][17][18][19][20]29,30,32,[34][35][36] ; some only mention Candida ssp [10,15,[22][23][24]28] . or specify the Candida subspecies [11,21,37,39] , or group Candida together with Aspergillus [25] or focus on one specific agent such as Malassezia [33] .…”
Section: Rate Of Fungal Microorganisms In the Included Series Of Infe...mentioning
confidence: 99%
“…The frequency of fungal native-valve endocarditis is largely unknown, however this disease affects nearly 0.1% of all prosthetic cardiac valves (9). Despite its rarity, Fungal endocarditis can present in any isolated heart valve or the combination of them (10)(11)(12)(13). Rising fungal endocarditis cases are attributed to improved diagnostic techniques, usage of immunosuppressants, invasive procedures, and the prevalent use of central venous catheters, which escalate the risk of medical-related IE.…”
Section: Introductionmentioning
confidence: 99%